Model Kesuksesan Pekerja Gig Kreatif Digital yang Dimoderasi oleh Modal Intelektual Individu pada Ekonomi Kreatif - Wendra, Wendra; Aryanto, riza; Besari, Humaira (Universitas Negeri Surabaya, 2023)
The creative economy sector contributes to the national gross domestic product. However, creative economy workers face precarious working conditions. So far, adequate research is needed on the success of creative sector gig workers who utilize online labour markets (OLMs) to interact with clients. This research aims to build a model that can describe the moderating role of individual intellectual capital on the relationship between job resources and digital creative gig workers' success. Survey data was collected from 197 gig creative digital workers. The statistical analysis was conducted with SmartPLS 4.0. The results of this study show that job demands have a negative and significant effect on the success of gig workers, job autonomy does not have a substantial impact on the success of gig workers, individual intellectual capital has a positive and significant effect on the success of gig workers, individual intellectual capital as a moderating variable influences the relationship between job demands and success of gig workers, individual intellectual capital as a moderating variable does not significantly influence the relationship between job autonomy and success of gig workers. This research creates the basis for future investigations that examine the direct and indirect associations between the job demand-resource model, individual intellectual capital, and gig worker success. By applying the job demand-resource model equipped with individual intellectual capital, the article suggests that gig workers, policymakers, policy executors, and educators must focus on investing in gig workers' intellectual capital to improve the gig worker's well-being.